The features of labor emigration from the Slovak Republic - Adriana Grenčíková; Ilona Skačkauskienė; Jana Španková (Verslas: Teorija ir praktika / Business: Theory and Practice, 2018)
Migration is historically a social phenomenon that not only has a significant effect on politics, economics, and social aspects but also presents challenges to the security of states and alters population composition in countries. Labor migration and its investigation are becoming a society-wide phenomenon because of the labor force shortage as well as the aging population. The Slovak Republic is a country that faces the outflow of qualified workers abroad, and the country's index of aging is one of the most dynamic in Europe. The current study aims at examining the relations and the reasons for emigration to work from the Slovak Republic. To identify the causes of labor emigration in the Slovak Republic, a survey was conducted to explore the decisions of people to emigrate for work, the duration of the stay abroad and the possibility of returning to Slovakia. This study also analyses the relationship between GDP growth and improvement of the economic situation in Slovakia, the number of labor emigrants, as well as the relationship between the minimum wage and the number of labor migrants.
Keywords: J11; F22; J61; J80; 650; migration; labor emigration; reasons for emigration; the minimum wage